Mathematical Analysis of a Two-Strain Compartmental Model with Vaccination and Quarantine - Teng, Timothy Robin (Archīum Ateneo, 2024)
We formulate a two-strain compartmental model that incorporates interventions such as vaccination and quarantine. The model is applicable for infectious diseases such as Influenza and COVID-19, and it's expressed as a system of ordinary differential equations. We establish the existence of four equilibrium solutions based on reproduction numbers R0,1 and R0,2, and threshold parameters R1 and R2. The local and global stability of each of these solutions is then analyzed, providing a long term outlook on epidemic progression. Numerical simulations that support the results on stability are also presented.